High burden of infectious disease and antibiotic use in early life in Australian Aboriginal communities. (6th February 2019) - Cuningham, Will; McVernon, Jodie; Lydeamore, Michael J.; Andrews, Ross M.; Carapetis, Jonathan; Kearns, Therese; Clucas, Danielle; Dhurrkay, Roslyn Gundjirryirr; Tong, Steven Y.C.; Campbell, Patricia T.
Abstract: Objective : To quantify the childhood infectious disease burden and antibiotic use in the Northern Territory's East Arnhem region through synthesis and analysis of historical data resources. Methods : We combined primary health clinic data originally reported in three separate publications stemming from the East Arnhem Healthy Skin Project (Jan‐01 to Sep‐07). Common statistical techniques were used to explore the prevalence of infectious conditions and the seasonality of infections, and to measure rates of antibiotic use. Results : There was a high monthly prevalence of respiratory (mean: 32% [95% confidence interval (CI): 20%, 34%]) and skin (mean: 20% [95%CI: 19%, 22%]) infectious syndromes, with upper respiratory tract infections (mean: 29% [95%CI: 27%, 31%]) and skin sores (mean: 15% [95%CI: 14%, 17%]) the most common conditions. Antibiotics were frequently prescribed with 95% (95%CI: 91%, 97%) of children having received at least one antibiotic prescription by their first birthday, and 47% having received six antibiotic prescriptions; skin sores being a key driver. Conclusions : Early life infections drive high antibiotic prescribing rates in remote Aboriginal communities. Implications for public health : Eliminating skin disease could reduce antibiotic use by almost 20% in children under five years of age in this population.